Stem rot of Dragon fruit (Hylocereus polyrhizus) caused by Fusarium species and its management - Prakash, Om; Akoijam Ratankumar (Umiam : CPGSAS, CAU, 2023)
Dragon fruit (Hylocereus polyrhizus) is an emerging crop. It is a herbaceous perennial climbing cactus species belonging to the family Cactaceae. Dragon fruit is more popular worldwide due to its attractive color, taste, sweet, juicy pleasant and nutritional richness with medicinal properties. The most destructive disease of dragon fruit is stem and fruit rot caused by Fusarium species with losses up to 40%. Morphologically different two Fusarium species (FMA and FMI) were isolated from different sites of ICAR NEH region Umiam, Meghalaya and identified by morphological, microscopic and molecular characteristics as Fusarium oxysporum and Fusarium longifundum. These Fusarium species showed significant variation in colony colour, growth rate, margin, pigmentation. The conidial size was maximum in F. oxysporum ((10.11-18.41 (Nh (B2.00- 3.65(So(Bm) and minimum in F. longifundum (2.3-6.7 (Nh (B1.6-2.03 (So(Bm). F. oxysporum was found more virulent as produce larger area of lesion (32.16 cm2) in pathogenicity test. In vitro evaluation of twenty four Trichoderma species as biocontrol agents against F. oxysporum, using dual culture method with three replications and found the best three Trichoderma spp. with the mycelial growth inhibition of T4 (T. harzianum) (91.48%), T6 (T. longibrachiatum) (90.76%) and T5 (T. erinaceum) (90.00%). In vitro evaluation of six botanicals extract from Allium sativum, Zingiber officinale, Curcuma augustifolia, Curcuma longa, Kaempferia rotunda and NEH plant extract using poison food technique against F. oxysporum revealed that ginger extract (5%) and NEH plant extract (10%) recorded the maximum per cent inhibition of 100 %. Similarly, in vitro efficacy of six fungicides like Azoxystrobin 45% + chlorothalanii 40%, Kasungmycin 5% + COC 45% WP, Carbendazim 12% + mancozeb 63%, Hexaconazole 5% SC, Fluopicolide 5.56% WW+ Propamocarb hydrochloride 55.6% WW and Chlorothalonil 75% WP was evaluated and found Kasungmycin 5% + COC 45% WP (0.05%) and Azoxystrobin 45% + chlorothalanii 40% (0.25%) recorded the maximum per cent inhibition of 100% and 87.77% respectively. Biochemical characterization of different Trichoderma species revealed T3 and T7 produce HCN, both T4, T12 (77.65%), T12 (75.84%) produce iron chelation efficiency, T10 (25.06 (So(Bg/ml), T6 (10.81 (So(Bg/ml) produce IAA, T8 (63.98%), T17 (55.21%) solubilize zinc and T12 (64.75%), T20 (54.40%) solubilize phosphorus. For the pot evaluation among the ten (10) treatments, T8 (combination of T. harzianum, T. longibrachiatum and T. erinaceum ) was found superior in plant height (55.60cm), number of branch (2), branch length (50.08 cm), cladode width (4.47 cm), arch height (0.48 cm), distance between areoles (4.82 cm) and number of spines (50.45), minimum disease severity index (0.00%) over control (80.00%). The efficacy of these best performed products must be further evaluated in the field condition and formulated for former$1 (Bs use. The technology for mass production of bio formulation may be developed for management of the disease.s
Includes bibliographical references and index.
Keywords: Dragon Fruit -- Diseases -- Management; Stem rot diseases -- Management; Botanical fungicides